Pengaruh Kualitas Layanan Akademik dan Fasilitas Pendidikan Terhadap Kepuasan Mahasiswa (Studi Kasus pada Mahasiswa Politeknik Bumi Akpelni Semarang) - Fatimah Azzahro, Fauziah; Utami, Tini; Luhur Pambudi, M Aji (Jurnal Maritim Polimarin, 2024)
The population of this study consists of 1,263 active Politeknik Bumi Akperni Semarang students in the academic year 2020-2021, and the purpose of this study is to determine the quality of academic services and educational facilities simultaneously and partially affect student satisfaction. The sample comprised 95 respondents, selected using a simple random sampling method. A Likert scale questionnaire, built on theory and transformed into instrumental variables, is used for data collection. Multiple regression analysis is also used to test the research instrument. The research results indicate that (1) the variable of academic service quality (X1) affects student satisfaction (Y), with a t-value of 2.917 greater than the t-table value of 1.986; (2) the variable of "educational institution" (X2) affects student satisfaction (Y), with a t-value of 4.192 greater than the t-table value of 1.986; and (3) the variable of academic service quality (X1) and the aspect of the educational institution (X2) affect student satisfaction. (Y).